2023
DOI: 10.3390/covid3050052
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of SARS-CoV-2 Infection in Ethiopia: A Systematic Review and Meta-Analysis

Abstract: Introduction: The Coronavirus disease of 2019 (COVID-19) is a catastrophic emerging global health threat caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). COVID-19 has a wide range of complications and sequelae. It is devastating in developing countries, causing serious health and socioeconomic crises as a result of the increasingly overburdened healthcare system. This study was conducted to determine the prevalence of SARS-CoV-2 infection in Ethiopia. Methods: Electronic databases, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 38 publications
(42 reference statements)
0
1
0
Order By: Relevance
“…Conversely, a SARS-CoV-2 seroprevalence study conducted from December 2020 to February 2021 in Ethiopia among health workers from public hospitals working in different regions of the country reported that the overall SARS-CoV-2 seroprevalence was 39.6% [20]. Furthermore, a systematic review in Ethiopia revealed that the pooled prevalence of SARS-CoV-2 infection was 8.8% [36].…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, a SARS-CoV-2 seroprevalence study conducted from December 2020 to February 2021 in Ethiopia among health workers from public hospitals working in different regions of the country reported that the overall SARS-CoV-2 seroprevalence was 39.6% [20]. Furthermore, a systematic review in Ethiopia revealed that the pooled prevalence of SARS-CoV-2 infection was 8.8% [36].…”
Section: Discussionmentioning
confidence: 99%